PENGARUH MODEL SNOW BALL THROWING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Ami, Siti Aminah; Amir Luthfi; M. Syahrul Rizal; Mufarizuddin; Yanti Yandri Kusuma (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of the snowball throwing learning model assisted by audio-visual media on improving the reading comprehension skills of fourth grade elementary school students. This research is classified as quasi-experimental research with samples taken using a purposive sampling technique. The research sample was students of class IVA and IVB at UPT SD Negri 035 Indrapuri. The instrument of this research is a test question. Statistical analysis was carried out using the Normality test, Homogeneity test, Independent Sample t-test. Based on the research results, data obtained with a value of tcount = 13.205 and ttable = 2.093 so that H1 can be accepted because the value of tcount > ttable. This shows that the reading comprehension skills for class IV elementary school with the snowball throwing model assisted by audio-visual media are higher than with the conventional learning model and it can be concluded that there is an influence of the snowball throwing model assisted with audio-visual media on improving reading comprehension skills for class IV elementary school.